Thymus and autoimmunity - Marx, Alexander; Yamada, Yosuke; Simon-Keller, Katja; Schalke, Berthold; Willcox, Nick; Ströbel, Philipp; Weis, Cleo-Aron Thias (Seminars in immunopathology, 2021)
The thymus prevents autoimmune diseases through mechanisms that operate in the cortex and medulla, comprising positive and negative selection and the generation of regulatory T-cells (Tregs). Egress from the thymus through the perivascular space (PVS) to the blood is another possible checkpoint, as shown by some autoimmune/immunodeficiency syndromes. In polygenic autoimmune diseases, subtle thymic dysfunctions may compound genetic, hormonal and environmental cues. Here, we cover (a) tolerance-inducing cell types, whether thymic epithelial or tuft cells, or dendritic, B- or thymic myoid cells; (b) tolerance-inducing mechanisms and their failure in relation to thymic anatomic compartments, and with special emphasis on human monogenic and polygenic autoimmune diseases and the related thymic pathologies, if known; (c) polymorphisms and mutations of tolerance-related genes with an impact on positive selection (e.g. the gene encoding the thymoproteasome-specific subunit, PSMB11), promiscuous gene expression (e.g. AIRE, PRKDC, FEZF2, CHD4), Treg development (e.g. SATB1, FOXP3), T-cell migration (e.g. TAGAP) and egress from the thymus (e.g. MTS1, CORO1A); (d) myasthenia gravis as the prototypic outcome of an inflamed or disordered neoplastic ‘sick thymus’.